Macht, Manipulation und Miteinander: Medienräume des Gerüchts - Sturm, Katharina (Nordlit, 2019)
‘Whoever rules over mankind’s stories shall be king.’—When Game of Thrones’ season eight ended, some considered this an answer too simple for eight seasons of fighting and suffering. It is this author’s opinion that this truth is beautiful just because it is humble. The following article does not consider ‘stories per se’, but a form of narrative, which is as much unique as it is ancient: ‘rumour’. If we consider rumour ‘to be a story’ and if we also allow the idea of stories to be powerful, rumour must appear as one of the strongest kind of narratives, as rumours do not only tell interesting myths; they also seem to provide ‘us’ with secret knowledge, with a little bit more truth than ‘those’, who did not hear it.Starting from a point of view where rumour is basically seen as an aesthetic phenomenon with strong emotional impact, the following article is going to ask how the rumour becomes interesting for both a psychoanalytical approach and a political one. Reasoning forward, the question shall be asked how this seemingly simple device of narration rises from emotion building to becoming a ‘true monster’, influencing mankind to the core of democracy. Or is it rather to be seen as a weapon for truly democratic participation? Notion is that both truths are true in their own way and that the relevant question actually should ask if the true ‘hero’ and/or ‘monster’ is not actually the one who carries this specific weapon. Due to this, the emotional impact rumours have, shall always be kept in mind during the following examination. Aim of this essay is, to bit-by-bit develop an idea of rumour, starting from an aesthetical regarding to a rather psychoanalytical and finally to a political, or rather society-affecting, point of view. In terms of structure and content, this essay aims to dig out rumour from a more sensual level of perception, to the concrete analysis of rumour as part of daily media consumption. The basic statement of this essay is that rumour can have the potential to become destructive, to ‘be a monster’, because we love it so dearly—and have been loving it for such a long time. In order to emphasize this notion, a rather wide and open historical frame is chosen, with the intention to pierce into current perceptions at times, just to illustrate the rumour’s ‘monstrosity’—but also to underline its inherent ‘ambiguity’.Editors’ Note: Sturm’s essay on the rumour’s potentially monstrous character (‘Authority, Manipulation, and Togetherness—Media Spaces of the Rumour’) appears in German. Its narrative mode can best be described as a colourful, multi-faceted stream of consciousness: From Adam and Eve via The War of the Worlds to ‘Netzwerkdurchsetzungsgesetz’; and beyond. From the worlds to the words: Those of our readers who may lack sufficient German proficiency, are encouraged to have a look at the English translation of Hans-Joachim Neubauer’s Fama (1998; 2009 [1998])—The Rumour (1999 [1998]). There are also Chinese, Croatian, Finnish, Japanese, Korean, and Spanish editions. A good read! See:Neubauer, Hans-Joachim. 1998. Fama: Eine Geschichte des Gerüchts. First German edition. Berlin: Berlin Verlag.Neubauer, Hans-Joachim. 1999 [1998]. The Rumour: A Cultural History. Translated by Christian Braun. First English edition. London/New York: Free Association Books.Neubauer, Hans-Joachim. 2009 [1998]. Fama: Eine Geschichte des Gerüchts. Second, extended and updated German edition. Berlin: Matthes & Seitz Berlin.
Keywords: rumour; secret [secrecy]; (media) society; social codes; informal exchange; blurred images; psychosomatics; Freudian bonus of seduction; public sphere; private sphere; social exclusion; ‘Fake News’; echo chambers [filter bubbles]; Network Enforcement Act